Anti-takeover provisions and executive excess compensation: evidence from China. Issue 3 (2nd July 2020) - Hu, Zhiying; Tong, Menglu; Liang, Shangkun
ABSTRACT: This article examines the effect of anti-takeover provisions on executive excess compensation and find a positive association. Five further findings are as follows. First, among specific provisions, the anti-takeover provisions mainly used to delay the takeover process have a stronger effect on executive excess compensation. Second, the positive effect of anti-takeover provisions on excess compensation is more significant in firms with higher executive power, less independent boards, and higher managerial myopia. Third, anti-takeover provisions have less effect on executive excess compensation in state-owned enterprises compared with non-state-owned enterprises. Fourth, the impact of the ownership structure on the anti-takeover provisions and excess compensation is non-linear. Fifth, the anti-takeover provisions decrease firm value, especially in those firms with more executive excess compensation. This article complements the literature on the anti-takeover provisions and executive compensation, which has great significance for the improvement of corporate governance.